Randomized Trial of Ceftazidime-Avibactam vs Meropenem for Treatment of Hospital-Acquired and Ventilator-Associated Bacterial Pneumonia (REPROVE): Analyses per US FDA–Specified End Points. (25th April 2019) - Torres, Antoni; Rank, Doug; Melnick, David; Rekeda, Ludmyla; Chen, Xiang; Riccobene, Todd; Critchley, Ian A; Lakkis, Hassan D; Taylor, Dianna; Talley, Angela K
Abstract: Background: Hospital-acquired and ventilator-associated pneumonia (HAP/VAP; nosocomial pneumonia) due to Gram-negative pathogens are associated with significant morbidity and mortality; treatment options for multidrug-resistant infections are limited. The pivotal phase III REPROVE trial evaluated the efficacy of ceftazidime-avibactam (CAZ-AVI) vs meropenem in the treatment of patients with HAP/VAP. Study results for prespecified analyses per US Food and Drug Administration–recommended trial end points are reported here. Methods: Hospitalized adults with HAP/VAP proven or suspected to be caused by a Gram-negative pathogen were randomized 1:1 to receive CAZ-AVI or meropenem for 7 to 14 days. The primary outcome was 28-day all-cause mortality in the intent-to-treat (ITT) population. Secondary outcomes included clinical cure at test of cure (TOC) in the ITT and microbiological ITT (micro-ITT) populations, and safety and tolerability throughout the study. Results: hundred seventy randomized patients received treatment and were included in the ITT population (CAZ-AVI, n = 436; meropenem, n = 434). CAZ-AVI was noninferior to meropenem for the primary end point (28-day all-cause mortality; ITT) based on the prespecified 10% noninferiority margin (CAZ-AVI, 9.6%; meropenem, 8.3%; difference, 1.5%; 95% confidence interval [CI], –2.4% to 5.3%) and for the clinical cure end point in the ITT population based on a prespecified –10% noninferiority margin (CAZ-AVI, 67.2%; meropenem, 69.1%; difference, −1.9%; 95% CI, –8.1% to 4.3%). Clinical cure rates at TOC for patients infected with CAZ-nonsusceptible pathogens were similar (CAZ-AVI, 75.5%; meropenem, 71.2%; micro-ITT). Safety data were consistent with established safety profiles for both agents. Conclusions: CAZ-AVI provides an important new treatment option for HAP/VAP due to Gram-negative pathogens, including CAZ-nonsusceptible strains.